2016
DOI: 10.1111/myc.12552
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of azoles as primary prophylaxis for the prevention of invasive fungal infections in Spanish patients undergoing allogeneic haematopoietic stem cell transplant

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A study of prophylactic triazole use in Spain predicted that voriconazole would be associated with higher costs than itraconazole; however, the analysis suggested that this would be partially offset by fewer IFIs and improved mortality. 24 Another economic evaluation of antifungal prophylaxis in the Netherlands suggested that using voriconazole as primary prophylaxis, followed by caspofungin, was more likely to provide cost-effectiveness than using liposomal AmB as primary prophylaxis. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of prophylactic triazole use in Spain predicted that voriconazole would be associated with higher costs than itraconazole; however, the analysis suggested that this would be partially offset by fewer IFIs and improved mortality. 24 Another economic evaluation of antifungal prophylaxis in the Netherlands suggested that using voriconazole as primary prophylaxis, followed by caspofungin, was more likely to provide cost-effectiveness than using liposomal AmB as primary prophylaxis. 33 …”
Section: Discussionmentioning
confidence: 99%
“…The model was designed from the perspective of institutional payers in charge of social security services in Mexico based on a similar decision-tree model used in an economic assessment of IFI prophylaxis in alloHSCT recipients in Spain, and verified by local clinical experts. 24 A decision-tree model was chosen based on the short time horizon of 6 months, the low number of disease states, and the low likelihood of disease recurrence. 25 The Instituto Mexicano del Seguro Social (IMSS) is the largest health care insurance system in Mexico, and publishes publicly available details of resource use and costs, which were used as sources for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of voriconazole and fluconazole prophylaxis in recipients of alloHSCT in the USA demonstrated that voriconazole was more cost-effective in a subset of patients with underlying acute myeloid leukemia (at a cost per life-year gained threshold of $50,000), most likely because of an inherently higher risk of IA in these patients [82]. More recently, a cost-effectiveness analysis comparing fluconazole, itraconazole, posaconazole, and voriconazole in recipients of alloHSCT in the Spanish healthcare system concluded that savings with voriconazole were likely to be in the region of €4707 per patient compared with oral posaconazole, with fewer deaths and IFIs with voriconazole [83]. Although the same study reported that prophylaxis with voriconazole results in higher total costs than with itraconazole, it was also associated with substantially fewer IFIs, resulting in an incremental cost of €212,101 per IFI avoided with voriconazole compared with itraconazole [83].…”
Section: Economic Impact Of Voriconazole Prophylaxismentioning
confidence: 99%
“…More recently, a cost-effectiveness analysis comparing fluconazole, itraconazole, posaconazole, and voriconazole in recipients of alloHSCT in the Spanish healthcare system concluded that savings with voriconazole were likely to be in the region of €4707 per patient compared with oral posaconazole, with fewer deaths and IFIs with voriconazole [83]. Although the same study reported that prophylaxis with voriconazole results in higher total costs than with itraconazole, it was also associated with substantially fewer IFIs, resulting in an incremental cost of €212,101 per IFI avoided with voriconazole compared with itraconazole [83]. Both of these economic evaluation analyses reported that costs relating to empirical therapy of breakthrough IFIs were reduced with voriconazole/mold-active prophylaxis.…”
Section: Economic Impact Of Voriconazole Prophylaxismentioning
confidence: 99%
“…In the clinic, invasive fungal disease is a serious problem with high mortality and morbidity rate, which could cause significant damage to human health, especially for hematological malignancies patients 6,7. As the first-line drug for the treatment of invasive aspergillosis, voriconazole (VOR) has a poor correlation between plasma levels and the drug dosing, because of its narrow therapeutic window (1.0–5.5 μg/mL) and variable pharmacokinetic profile 8,9.…”
Section: Introductionmentioning
confidence: 99%